PROFIL RESPON SISWA PENGGUNAAN E-MODUL FISIKA BERBASIS ANDROID (ANDROMO) - Nofefta Gola; Subiki Subiki; Lailatul Nuraini (JURNAL PEMBELAJARAN FISIKA, 2022)
Covid-19 has an impact on all activities, one of which is education. This causes learning to turn into a distance learning system. Physics is a subject that is considered difficult for students to reach. The purpose of this research was to analyze the responses of Ngoro Jombang Senior High School students after using physics e-module based android (andromo), the subject of elasticity. This research method has a quantitative research method using an instrument in the form of a response questionnaire given to class XI MIPA of of Ngoro Jombang Senior High School. Based on the research that has been done, it shows that physics e-module based android (andromo) gets a positive response from respondents. The physics e-module based android (andromo) gets an average score of 71.95% from respondents. Key word: student response, e-module, andromo